Non-Invasive Biomarkers and Breath Tests for Diagnosis and Monitoring of Chronic Liver Diseases - Pasawat Boon-yasidhi; Wikrom Karnsakul (Diagnostics)
Background: Chronic liver disease (CLD) presents a significant global health burden, demanding effective tools for diagnosis and monitoring. Traditionally, liver biopsy has been the gold standard for evaluating liver fibrosis and other chronic liver conditions. However, biopsy’s invasiveness, associated risks, and sampling variability indicate the need for reliable, noninvasive alternatives. This review examines the utility of noninvasive tests (NITs) in assessing liver disease severity, progression, and therapeutic response in patients with CLD. Result: Key modalities discussed include serum biomarker panels (e.g., FIB-4, APRI, ELF), imaging techniques like transient elastography, and magnetic resonance elastography, each offering unique benefits in fibrosis staging. Emerging biomarkers such as extracellular vesicles and circulating microRNAs show promise in early detection and personalized monitoring. Comparative studies indicate that while no single NIT matches biopsy precision, combinations of these modalities improve diagnostic accuracy and patient outcomes by reducing unnecessary biopsies. Moreover, NITs are instrumental in monitoring dynamic changes in liver health, allowing for more responsive and patient-centered care. Conclusions: Challenges remain, including standardization across tests, cost considerations, and the need for larger, diverse population studies to validate findings. Despite these limitations, NITs are increasingly integrated into clinical practice, fostering a paradigm shift toward noninvasive, accessible liver disease management. Continued advancements in NITs are essential for improved patient outcomes and will likely shape the future standard of care for CLD.